FASILITAS OBJEK WISATA PASAR WISATA KOTA PEKANBARU - Patrick Joshua Hutapea; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This reserch is about the attraction of tourist facilities Pekanbaru Travel Market. Thepurpose of this study are: (1) to assess the attraction facilities Pekanbaru Travel Market, (2) todetermine the expectations of visitors to the existing facilities at the attraction Travel MarketPekanbaru.The sample in this study is the tourists who visited attraction Travel Market PekanbaruCity in 2014, amounting to 94 560 people, who then uses a formula to determine besara slovinsample. So it can be determined the number of samples in this study is 100 people. This studyused a qualitative descriptive method in determining the outcome of the study.The results of this study is stated that the level of satisfaction of visitors to the attraction oftourist facilities in the city of Pekanbaru Travel Market is good enough. It can be seen from theresults of questionnaires, observations and interviews that researchers do in the field.The conclusions in research on tourist facilities attraction Pekanbaru Travel Market are: (1)Given that the existing tourist facilities in the tourism market, both major facilities, supportfacilities, and supporting facilities have been considered quite good. (2) Given that visitors whocome to the tourist market still has high expectations of improvement of tourist facilities in thelocation of the tourist market.Keywords: Tourism Facilities, Top Facilities, Facility Support, Supporting Facilities, Attractions,Travel Market, visitor satisfaction.